Synthesis and anti-HIV activity of [d4U]-spacer-[HI-236] bifinctional HIV-1 reverse transcriptase inhibitors - Muhanji, Clare Imbosa (Department of Chemistry, 2014)
Includes bibliographical references (leaves 182-190).